Avaliação do Sistema Eletrônico de Informações (SEI) em uma instituição federal de ensino superior - Lourenço, Elrick de Oliveira (2019)
The computerization of administrative processes has been one of the great challenges of public management. In Brazil, an IT solution was successfully used in the judicial administration to enable the Electronic Information System (SEI) in all spheres of the Brazilian public sector. Thus, the research aimed to evaluate the SEI in a federal public institution of higher education, based on the dimensions of the Delone and McLean model (2003) and adapted by Wang and Liao (2008) in order to verify if such a system could be considered a success in the public sector. The results were tested through hypotheses that demonstrated a significant impact of the quality of the information and quality of the system in its use. They also affirmed that the quality of the service has a strong relationship with user satisfaction, and the use of the system and user satisfaction are determining factors for the perception of the benefits generated by the SEI.